Effectiveness of the Buzzy Bee device on pain perception during invasive pricks among school age children: An interventional study - Ghadeer Al Battashi; Zainab Said AL-Shibli; Abeer Issa Alghafri; Omar Mohammed Alyazeedi; Ali Saif Alkalbani; Frincy Francis; G Gopakumar (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Children often develop phobia toward needle pricks and invasive procedures. It is difficult for medical personnel to manage children's pain when they are in the hospital. When it comes to assessing and treating children's discomfort, nurses interact with them the most. The main objective of the study was to evaluate the effectiveness of the Buzzy Bee device on pain perception among children undergoing invasive needle pricks as part of their treatment. MATERIALS AND METHODS: The study used a quantitative approach with a quasi-experimental design employing simple random sampling. A post-test-only design was used. After obtaining ethical clearance, data collection was done in the pediatric outpatient department and pediatric wards of Sultan Qaboos University Hospital, Muscat, Oman, between February 2020 and August 2021. Faces Pain Rating Scale for children was used to rate the pain during the procedure, which is a standardized tool. Data were analyzed using SPSS version 23. Descriptive and inferential statistical tests were done to analyze the data. RESULTS: Totally, 120 children along with their parents were interested in the study. After taking appropriate parental consent and children's assent, the participants were recruited by simple random sampling. They were equally divided into 60 in the experimental group and 60 in the control group. The mean age was 8.14 (+/-2.3) in both groups. Among the 120 samples, 63 (52.5%) of them were males and 57 (47.5%) were females. The majority of them had diagnoses like thalassemia, leukemia, and sickle cell and were getting cannulated for blood transfusion therapy. t-test shows that 51.7% (31 samples) reported no pain in the experimental group and 33.3% (20 samples) reported only mild pain, whereas in the control group, only 5.0% (3 samples) reported no pain and 21.7% (13 samples) reported mild pain. About 26.7% of the samples reported very much pain as against the 7% who reported very much pain in the interventional group. There was a statistically significant difference in the pain scores between the control group and the experimental group (likelihood ratio test, P = 0.0001). The Buzzy Bee method significantly reduced the pain. CONCLUSION: The introduction of a toy-like, child-friendly device, which works on the mechanism of vibrations and cold application, lessened the pain intensity during the procedure and acted as a good distractive therapy for children.